2015
DOI: 10.1111/his.12468
|View full text |Cite
|
Sign up to set email alerts
|

Using frozen section to identify histological patterns in stage I lung adenocarcinoma of ≤3 cm: accuracy and interobserver agreement

Abstract: Aims The IASLC/ATS/ERS classification of lung adenocarcinoma provides a prognostically significant histologic subclassification. The aim of this study is to investigate the accuracy, limitations, and interobserver agreement of frozen sections (FS) for predicting histologic subtype. Methods and results FS and permanent section slides from 361 resected stage I lung adenocarcinomas ≤ 3 cm were reviewed for predominant histologic subtype and presence or absence of lepidic, acinar, papillary, micropapillary, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
121
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(135 citation statements)
references
References 48 publications
9
121
5
Order By: Relevance
“…We found a 'moderate' agreement for the primary pattern, and only a 'fair' agreement for the secondary pattern. Our findings are similar to that of Yeh et al, 19 who reported unsatisfactory accuracy of frozen sections for histologic subtyping with also only 'moderate' agreement …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found a 'moderate' agreement for the primary pattern, and only a 'fair' agreement for the secondary pattern. Our findings are similar to that of Yeh et al, 19 who reported unsatisfactory accuracy of frozen sections for histologic subtyping with also only 'moderate' agreement …”
Section: Discussionsupporting
confidence: 91%
“…This is similar to results reported by Yeh at al. 19 Interestingly, lepidicpredominant tumors showed a low sensitivity in our study (33.3%) and a very high specificity (94.4%). This result might be related to the fact that lepidicpredominant tumors showed a combination of acinar and lepidic patterns on the frozen sections and therefore were most frequently misclassified as acinar-predominant.…”
Section: Modern Pathology (2015) 28 1058-1063contrasting
confidence: 65%
See 1 more Smart Citation
“…In a recent review of 361 resected stage I adenocarcinomas ≤3 cm frozen section analysis had a high specificity but low sensitivity for micropapillary and solid patterns (27). In a retrospective study of 803 patients with stage I adenocarcinoma the concordance rate between frozen section analysis and final pathology was 84.4% (28).…”
Section: Editorialmentioning
confidence: 98%
“…Particular attention was also paid to the identification of a micropapillary pattern, which was recognized with a 98% specificity rate when identified but was recognized with only a 13% sensitivity rate. Similarly, Yeh et al, evaluated 361 resected stage 1 ADCs in regard to accuracy of pattern identification, and additionally attempted to evaluate the accuracy of the presence of invasion at the time of frozen section in 35 cases (46). Similar to the Trejo Bittar study, agreement on the predominant histologic subtype achieved only a moderate a kappa value of 0.565 and again showed high specificity but low sensitivity for the identification of a micropapillary component.…”
Section: Treatment Implications Of the New Classification Systemmentioning
confidence: 99%